Settlement Spatial Planning Reconstruction Site Umah Pitu Ruang - Cahayani, An’gun; Muliadi; Waulandari, Elysa; Jamaludin, Masdar (Rumoh Journal of Architecture, 2023)
The spatial arrangement patterns of rural areas are generally closely related to the natural environment and surrounding ecological, spiritual, and theological values. Kampung Genuren, the location chosen for the reconstruction of the Umah Pitu Ruang, is characterized by the presence of agricultural and plantation lands within its residential area. Moreover, Kampung Genuren is one of the traditional villages that still adheres to the Gayo cultural system, with a well-preserved rural atmosphere—both in terms of the local community’s activities and the environmental conditions. These characteristics make Kampung Genuren an appropriate site for the Umah Pitu Ruang reconstruction. The community's cultural practices and land use patterns help reveal various potential characteristics of the spatial settlement pattern in Kampung Genuren. These elements form the analytical foundation for identifying both opportunities and challenges that may arise at the study site, particularly in relation to the location and process of the Umah Pitu Ruang reconstruction, which is the main objective of this research. Based on field findings, the researcher conducted a site study using a descriptive qualitative method. The analysis of existing conditions was supported by map-based analysis through several stages to obtain primary data, which then served as a reference for identifying the spatial pattern characteristics of Kampung Genuren. The research was conducted over approximately three months. The initial stage involved collecting secondary data, followed by the acquisition of primary data through several journal references. These data were then processed and described using field documentation results, and visualized in map form using software applications such as ArcGIS, Google Earth, satellite imagery, and other supporting tools. The research concludes that several supporting facilities in the form of nearly extinct traditional buildings will be provided as a means to revive and preserve Gayo culture through the reconstruction of Umah Pitu Ruang.